2020
DOI: 10.1016/j.radonc.2020.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Local dose analysis to predict acute and late urinary toxicities after prostate cancer radiotherapy: Assessment of cohort and method effects

Abstract: To perform bladder dose-surface map (DSM) analysis for (1) identifying symptomrelated sub-surfaces (Ssurf) and evaluating their prediction capability of urinary toxicity, (2) comparing DSM with dose-volume map (DVM) (method effect), and (3) assessing the reproducibility of DSM (cohort effect).Methods and materials: Urinary toxicities were prospectively analyzed for 254 prostate cancer patients treated with IMRT/IGRT at 78/80Gy. DSMs were generated by unfolding bladder surfaces in a 2D plane. Pixel-by-pixel ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In addition to removing programming barriers, the accessibility of rtdsm has the potential to improve DSM reproducibility between groups, which is becoming an area of concern as the methodology gains in popularity. Mylona et al 35 recently reported poor reproducibility of toxicity-predictive subregions from bladder DSMs of prostate patients when comparing their results to three other studies. Despite similar DSM construction and analysis approaches, it appears variations in vertical mapping methods between groups (scaled mapping by Mylona, 1:1 mapping truncated at 25 or 45 mm by others 5,13 36 ) influenced the reproducibility of results.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to removing programming barriers, the accessibility of rtdsm has the potential to improve DSM reproducibility between groups, which is becoming an area of concern as the methodology gains in popularity. Mylona et al 35 recently reported poor reproducibility of toxicity-predictive subregions from bladder DSMs of prostate patients when comparing their results to three other studies. Despite similar DSM construction and analysis approaches, it appears variations in vertical mapping methods between groups (scaled mapping by Mylona, 1:1 mapping truncated at 25 or 45 mm by others 5,13 36 ) influenced the reproducibility of results.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to removing programming barriers, the accessibility of rtdsm has the potential to improve DSM reproducibility between groups, which is becoming an area of concern as the methodology gains in popularity. Mylona et al 35 . recently reported poor reproducibility of toxicity‐predictive subregions from bladder DSMs of prostate patients when comparing their results to three other studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…None of the DV metrics were selected during MVA. Moving forward, this study could be expanded to incorporate the use of dose surface maps (DSM) analysis with spatial information for the model-building to improve spatial dose–response correlations [51] . In addition, work is in progress to apply this model to determine the feasibility of performing dose escalation or hypofractionated regimens as well as incorporating advanced modalities, such as proton therapy to enhance the patient’s therapeutic ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Voxel-wise analysis by non-rigid registration has become a well-established methodology able to unveil the likely heterogeneous radiosensitivity across the organs, which may be helpful in the identification of sub-regions to be spared at the planning step. One of the major advantages of the voxel-wise analysis is its ability to explore the full 3D anatomy without prior assumptions regarding the location of regions correlating with toxicity (25). As compared with dose surface maps, which have also been used for this purpose, the voxel-based methods present the advantage of generating 3D volumes that can be transferred to the clinical practice in a straightforward way.…”
Section: Discussionmentioning
confidence: 99%